2016
DOI: 10.1037/hea0000318
|View full text |Cite
|
Sign up to set email alerts
|

The role of caregiver social support, depressed mood, and perceived stress in changes in pediatric secondhand smoke exposure and asthma functional morbidity following an asthma exacerbation.

Abstract: Objective Caregiver depressed mood and stress are associated with increased child asthma functional morbidity (AFM) and secondhand smoke exposure (SHSe), while social support (SS) reduces risk. This study extends previous literature by examining: (1) longitudinal patterns of pediatric AFM and SHSe and (2) how caregiver stress, depressed mood, and SS are related to child SHSe and AFM changes. Methods Participants were 334 caregivers who smoked, had a child with asthma, and who were enrolled in a smoking cessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Social support also emerged as a consistent predictor of life stress, with high levels of emotional/ informational support associated with reduced life stress in the mothers. Social support was previously identified as a salient factor to explore in relation to child asthma functional morbidity and second-hand smoke exposure [23], and our findings similarly emphasize its importance as a potential protective mechanism for self-reported life stress. However, contrary to expectations, social support failed to moderate the observed relationships between home and community hardships and life stress.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Social support also emerged as a consistent predictor of life stress, with high levels of emotional/ informational support associated with reduced life stress in the mothers. Social support was previously identified as a salient factor to explore in relation to child asthma functional morbidity and second-hand smoke exposure [23], and our findings similarly emphasize its importance as a potential protective mechanism for self-reported life stress. However, contrary to expectations, social support failed to moderate the observed relationships between home and community hardships and life stress.…”
Section: Discussionsupporting
confidence: 76%
“…Since impoverished caregivers who encounter a high number of home and community hardships are more likely to endorse clinically significant depressive, anxiety, and trauma symptomatology [21,22], and have children with greater asthma morbidity [23], it is important to identify and develop responsive interventions for the sources of life stress. However, the limited studies examining life stress experienced by caregivers of children with asthma are primarily cross-sectional and fail to differentiate the relative contribution of asthma-specific, sociodemographic, and home and community-level risk experiences on stress over time.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of poorly controlled asthma are multifactorial and include environmental exposures to triggers in the home and community (e.g., second hand smoke, rodents, mold, dust mites), poor condition knowledge and self-management skills, access to care barriers including difficulties with medication administration in the school, and hardships associated with poverty (Authors, 2014 Authors, 2017a; Borowsky et al, 2013; Bruzzesse et al, 2012; Camacho-Rivera et al, 2014; Lang et al, 2013; Ungar, Cope, Kozyrskyj, & Paterson, 2010). Caregiver psychosocial factors such as life stress and depressive symptoms further heighten risk for child asthma morbidity (Authors, 2015; Clawson et al, 2016; Feldman et al, 2011, 2013; Lim, Wood, Miller, & Simmens, 2011; Martin et al, 2013; Tibosch, Verhaak, & Merkus, 2011). To improve asthma control and reduce asthma health disparities, a range of home, community, and ED based interventions have been developed (Pinnock et al, 2017; Welsh et al, 2011), but the suboptimal outcomes for low-income, minority children persist.…”
Section: Introductionmentioning
confidence: 99%
“…Purposive sampling methods were used to recruit caregivers who had completed the RCT and agreed to be contacted for future asthma studies. Since maternal depression and life stress are associated with greater risk for child asthma morbidity and impaired caregiver quality of life (Authors, 2015; Clawson, Borrelli, McQuaid, & Dunsiger, 2016; Martin et al, 2013; Otsuki et al, 2010; Pak & Allen, 2012; Shalowitz, Berry, Quinn, & Wolf, 2001), study staff sent letters inviting 37 caregivers who reported clinically significant depressive symptoms (CES-D score ≥ 16; Radloff, 1977) or high life stress scores (Visual Analogue Scale of daily life stress score ≥ 6 where stress 1=no stress, 10=highest possible stress) at 12-month follow-up to participate in the individual interviews. Interested caregivers (n=12) contacted the study office, received additional details about the purpose of the study, and consented to be interviewed.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between asthma control and achievement of caregiver cotinine levels (high or low status) were investigated by crude odds ratios and adjusted odds ratios. Adjusted odds ratios applied logistic regression modelling using variables previously described as correlates of adult smoking behaviors [ 40 , 41 ]. Confidence intervals (95%) were calculated for both crude and adjusted odds ratios.…”
Section: Methodsmentioning
confidence: 99%